Glial cell-line derived neurotrophic factor is essential for electroconvulsive shock-induced neuroprotection in an animal model of Parkinson's disease - Anastasia Gonzalez, Agustin (2011)
Sustained motor improvement in human patients with idiopathic Parkinson's disease has been described following electroconvulsive shock (ECS) treatment. In rats, ECS stimulates the expression of various trophic factors (TFs), some of which have been proposed to exert neuroprotective actions. We previously reported that ECS protects the integrity of the rat nigrostriatal dopaminergic system against 6-hydroxydopamine (6-OHDA)-induced toxicity; in order to shed light into its neuroprotective mechanism, we studied glial cell-line derived neurotrophic factor (GDNF) levels (the most efficient TF for dopaminergic neurons) in the substantia nigra (SN) and striatum of 6-OHDA-injected animals with or without ECS treatment. 6-OHDA injection decreased GDNF levels in the SN control animals, but not in those receiving chronic ECS, suggesting that changes in GDNF expression may participate in the ECS neuroprotective mechanism. To evaluate this possibility, we inhibit GDNF by infusion of GDNF function blocking antibodies in the SN of 6-OHDA-injected animals treated with ECS (or sham ECS). Animals were sacrificed 7 days after 6-OHDA infusion, and the integrity of the nigrostriatal system was studied by tyrosine hydroxylase immunohistochemistry and Cresyl Violet staining. Neuroprotection observed in ECS-treated animals was inhibited by GDNF antibodies in the SN. These results robustly demonstrate that GDNF is essential for the ECS neuroprotective effect observed in 6-OHDA-injected animals.